# Equation 5013

Solve the equation in quotient form:

6x * (3x-2) / x + 7 = 0

6x * (3x-2) / x + 7 = 0

### Correct answer:

Tips for related online calculators

Are you looking for help with calculating roots of a quadratic equation?

Do you have a linear equation or system of equations and looking for its solution? Or do you have a quadratic equation?

Do you have a linear equation or system of equations and looking for its solution? Or do you have a quadratic equation?

#### You need to know the following knowledge to solve this word math problem:

## Related math problems and questions:

- Equations: 43501

Solve two equations: 7 * (x + 1) - (3x + 1) = 21/2 a / 3-a + 6/12 = 2a-4 - Equation

Solve the equation and check the result: 1.4x - 3/2 + x - 9,8 = x + 0,4/3 - 7 + 1,6/6 - Equation: 25581

Solve the equation: (7x-1) / 3 + (5 + 3x) / 2 = 5x - 6 - Inequality: 3538

Example1: Solve a linear equation and perform a test: 6x- (3x + 2) = x-8 Example 2: Solve a linear inequality: 3y + 2 * (y + 1) ≥2y-7 - Solve 18

Solve simple equation: 3x = 5x + 6/2x + 3 - Interesting 8981

Solve an interesting equation: (1 * x) + (2 * x) + (3 * x) + (4 * x) + (5 * x) + (6 * x) = 100 - Following 1859

Solve the following linear equation in R: 4 / 10X + 2 / 10X + 1 / 6X + 1 / 10X + 400 = X - Equation: 6200

Solve the equation: 2y = 4 (0.5 + 3/2) -1 - Equations 5070

Solve in RxRxR a system of 3 linear equations with three unknowns: 1/2 x + 3/4 y = 6z 2x-z = 10 1/2 2z + x = 2y + 7 note : / is a fraction line - Logarithmic equation

Solve equation: log_{13}(7x + 12) = 0 - Simple equation 6

Solve the equation with one variable: X/2+X/3+X/4=X+4 - Equation: 6645

Solve the equation: (2v + 2) / 8 = (v-7) / 4-v - Polynomial: 8465

Solve the equation with the polynomial: x / 2 + 1/2 + 3 = x - EQ2

Solve a quadratic equation: 2x²- 2(x-7)²+5x=0 - Equation 3364

Create a number snake from the equation and solve: 2x - 5 = 7 4x + 1/3 = 7 3 (x-2) +4 = 7 - Reciprocal equation 2

Solve this equation: x + 5/x - 6 = 4/11 - Simple equation 8

Solve the following equation: 36=-(1+7x)-6(-7-x)